Bird migration in space and time: chain migration by Eurasian curlew Numenius arquata arquata along the East Atlantic Flyway - Pederson, Rebecca; Bocher, Pierrick; Garthe, Stefan; Fort, Jérôme; Mercker, Moritz; Auernhammer, Verena; Boschert, Martin; Delaporte, Philippe; Elts, Jaanus; Fiedler, Wolfgang; Korniluk, Michał; Krupiński, Dominik; et al. (Journal of Avian Biology, 2022)
International audience